Modelagem paramétrica e FFT aplicadas à investigação do conteúdo espectral de uma carga de 15 MW acionada por cicloconversor - Raphael Villani de Castro (2018)
This work presents a practical application of signal processing techniques on the investigation of the current spectral content of an electrical equipment. The studied equipment is composed by a set of a cycloconverter and a synchronous motor, which is responsible for the driving of a load of 15 MW average demand. The author further develops a previous consulting project provided to a mining industry on the characterization of its ore processing facilities to improve the electrical system reliability. As its main objective, this work aimed at the refinement of techniques to characterize the equipment electrical current under normal operation in terms of frequency content, with all information based on 211 measurements of 200ms time window taken with a Power Quality Analyzer, and the confrontation of the results obtained with the spectrum information made available by the manufacturer. The techniques, based on the Fast Fourier Transform and in Parametric Modelling using Steiglitz-McBride method, have their results compared and, Parametric Modelling results, which were found to be superior in modelling the current waveforms, are compared to the spectrum informed by the manufacturer. From the comparisons, the author discusses how the manufacturers criteria for system simulation should be improved to better depict the reality of the client and to facilitate the design of harmonic filtering systems.